Perceived facial happiness during conversation correlates with insular and hypothalamus activity for humans, not robots - Chaminade, Thierry; Spatola, Nicolas (Frontiers in Psychology, 2022)
Emotional contagion is essential to create social bonds, in particular for happiness. The Somatic Marker Hypothesis posits that embodied physiological changes associated with emotions and relayed to the brain by the autonomous nervous system influence behaviour. Perceiving others' positive emotions should thus be associated with activity in brain regions relaying information from and to the autonomic nervous system. Here, we address this question using a unique corpus of brain activity recorded during unconstrained conversations between participants and a human or a humanoid robot. fMRI recordings are used to test whether activity in key brain regions pertaining to the autonomic system, the amygdala, hypothalamus and insula, is differentially affected by the level of happiness expressed by the human and robot agents. Results indicate that for the hypothalamus and the insula, in particular the anterior agranular region strongly involved in processing social emotions, activity in the right hemisphere increases with the level of happiness expressed by the human, but not the robot. Altogether, perceiving positive emotions in social interactions induces local brain responses predicted by the somatic marker hypothesis only when the interacting agent is a fellow human.